2015
DOI: 10.1002/app.42988
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigation of sound transmission loss for polycarbonate, poly(methyl methacrylate), and glass

Abstract: In this study, the effects of the soundproofing properties of polycarbonate (PC), poly(methyl methacrylate) (PMMA), and glass were investigated. We fabricated the specimens into 3 mm thick sheets by direct hot compression molding as a monolithic sample and also by gluing three thin sheets together into a multilayer. Sound transmission loss (STL) was measured by an impedance tube over the frequency range 63-1600 Hz. The results indicate that because of the close density, the STLs for PC and PMMA were almost the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Sabet et al. [323] investigated the noise insulation of the polycarbonate (PC), poly (methyl methacrylate) (PMMA), and glass. They measured the STL via ITM over the frequency domain between 63normal andnormal 1600normal |Hz.…”
Section: Vibroacoustic Solutionmentioning
confidence: 99%
“…Sabet et al. [323] investigated the noise insulation of the polycarbonate (PC), poly (methyl methacrylate) (PMMA), and glass. They measured the STL via ITM over the frequency domain between 63normal andnormal 1600normal |Hz.…”
Section: Vibroacoustic Solutionmentioning
confidence: 99%
“…[34,36] Several studies of transmission loss for sandwich and composite DPS have revealed various important regions [33]. However, the transmission loss characteristics curve can be generally divided into three regions-the stiffness controlled region, the mass controlled region and the coincidence controlled region [34,[37][38][39][40][41] as depicted in Figure 1. From the figures, the stiffness controlled region emanating from the origin to the first resonance ( f R ) for flat plate or the transition resonance ( f r ) for cylindrical or curved shell, is seen as a falling STL curve in the low frequency region.…”
Section: Symbol Formula Definition Referencementioning
confidence: 99%
“…As the king of commercial engineering plastic, polycarbonate (PC) has become an important raw material for high‐value‐added products, such as 5G communications, translucent construction facades, aircrafts, and medical supplies 1 . Nowadays, with the application of high‐end products, the mechanical behavior, 2,3 flame retardant, 4,5 sound insulation, 6,7 thermal 8,9 and optical 10,11 properties of PC have received widespread attention. Among them, environmental stress cracking is a serious issue in PC when the conditions of pre‐strain and the presence of fluid with a compatible solubility index are both prevalent, resulting in an order of magnitude less than the actual tensile 12 .…”
Section: Introductionmentioning
confidence: 99%